2017
DOI: 10.1089/thy.2016.0348
|View full text |Cite
|
Sign up to set email alerts
|

RAS Mutations, and RET/PTC and PAX8/PPAR-gamma Chromosomal Rearrangements Are Also Prevalent in Benign Thyroid Lesions: Implications Thereof and A Systematic Review

Abstract: The presence of these biomarkers and the tremendous variation in reports of their prevalence in benign lesions suggests the need for caution when including these markers in diagnostic decisions. Further understanding of the importance of these markers, as well as newly discovered markers of thyroid malignancy, may be required in order to avoid overtreatment of patients with benign thyroid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 80 publications
2
37
0
2
Order By: Relevance
“…Despite the high specificity of BRAFV600E and RET/PTC as markers of malignancy, 13 the clinical usefulness of the 7-gene test we used is limited by the low specificity and low positive predictive value of RAS and RAS-like mutations (PAX8/PPARg and BRAFK601E) because these mutations are also detected in such benign thyroid nodules as follicular adenomas. [14][15][16] In addition, the indolent encapsulated PTC follicular variant recently reclassified as a low-risk neoplasm (noninvasive follicular thyroid neoplasm with papillary-like nuclear features [NIFTP]) accounts for a large proportion of RAS-mutated nodules. 17 However, it remains to be established whether mutation-positive adenomas and NIFTP are follicular-patterned in situ carcinomas and should be considered as true-positives in the evaluation of the positive predictive value of the 7-gene test.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high specificity of BRAFV600E and RET/PTC as markers of malignancy, 13 the clinical usefulness of the 7-gene test we used is limited by the low specificity and low positive predictive value of RAS and RAS-like mutations (PAX8/PPARg and BRAFK601E) because these mutations are also detected in such benign thyroid nodules as follicular adenomas. [14][15][16] In addition, the indolent encapsulated PTC follicular variant recently reclassified as a low-risk neoplasm (noninvasive follicular thyroid neoplasm with papillary-like nuclear features [NIFTP]) accounts for a large proportion of RAS-mutated nodules. 17 However, it remains to be established whether mutation-positive adenomas and NIFTP are follicular-patterned in situ carcinomas and should be considered as true-positives in the evaluation of the positive predictive value of the 7-gene test.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies with the 7‐gene mutation panel indicated that rat sarcoma (RAS) (a family of small guanosine triphosphate hydrolases) mutations were most common but were not highly specific for thyroid cancer, thereby limiting the PPV of the test. Recent studies have demonstrated that RAS mutations also can be identified in up to 48% of benign nodules; therefore, the type of RAS mutation and the degree of allelic frequency can be used to guide decision‐making . Similarly, many thyroid nodules with RAS and PAX8/PPARγ mutations are the histologically noninvasive encapsulated follicular variant of PTC, now reclassified as NIFTP .…”
Section: The Development Of Thyroid Molecular Testingmentioning
confidence: 99%
“…However, BRAF mutation does not appear to improve prognosis or direct treatment beyond traditional TNM classifications, and the independent use of BRAF would incorrectly upstage the majority of indolent behaving, lower stage classical PTCs. Furthermore, it has been demonstrated that certain RAS mutations have a higher likelihood of distant metastasis and increased mortality compared with BRAF mutations, but RAS mutations can also be identified in benign follicular adenomas and in the noninvasive encapsulated follicular variant of PTCs (NIFTP), now reclassified as a premalignant tumor . Two molecular markers that appear to confer an increased risk of tumor recurrence and tumor‐related mortality are tumor protein 53 (TP53) and telomerase reverse transcriptase (TERT) mutations.…”
Section: Comprehensive Tests To Improve Overall Accuracymentioning
confidence: 99%
See 2 more Smart Citations